“Publish or not”: an output problem of higher education students - Nasution, Ummi Aisah; Afanin Nabila; Sholihatul Hamidah Daulay (UNIB Press, 2024)
Publication is an important activity for students studying at university, especially for those who are completing their thesis or final project. The aim of this research is to know problems experienced by students during the publication process and students' perceptions about the output of article publications to obtain a master's degree in the English education master's department, is it better “publish or not”?. The researcher uses a descriptive qualitative method and interviews as a data collection technique for two students in Higher Education especially master’s students of English education. The results of this finding are there are several problems experienced by students during the article publication process: articles that were rejected by the journal, so they had to look for another journal and it would take a long time. It takes quite a long time to get to the publication stage because as said by participants, each journal has provisions for the publication stage how many times a year and wait for the article review stage which was quite long. And both participants chose